Patterns of Aggressive Behaviors Across Mental Health in Sixth Graders - DuPont-Reyes, Melissa J. (Journal of interpersonal violence, 2021)
School-based violence is a current public concern in the United States. One factor that can impact school-based violence that has gained much attention is mental health status. To better inform public perceptions, this study provides new evidence concerning the association between mental health status and acting out violence in school-aged populations. We examined a diverse sample of sixth graders across 14 schools in Texas in 2011-2012 (N = 721) who completed a self-administered survey assessing mental health symptoms and frequency of perpetration and/or receipt of different types of aggressive behaviors. Multinomial regression models tested whether adolescents with mental health symptoms (overall and by symptom types) are more predisposed to be actors only, recipients only, or both, of physical, verbal, and relational aggression. Across aggressive behavior types, symptomatic versus nonsymptomatic adolescents had consistently increased odds of being exclusively a recipient of aggression. When symptomatic adolescents did act out aggression, they participated concurrently as both an actor and recipient. Rarely were symptomatic adolescents more likely to be exclusively an actor of aggression. Moreover, symptomatic versus nonsymptomatic adolescents had five times the odds of being threatened by a weapon including a gun or knife. Compared to those who do not, youth who perceive having a mental health issue had twice the odds of being an actor only of verbal and relational aggression. These findings provide evidence for the need to change how the public associates mental health problems with aggressive behaviors among youth especially following national tragic events. Communities at large may benefit from evidence- and school-based interventions that improve awareness of and tolerance to mental health conditions among youth.